Drug therapy in Pediatric Scrub Typhus – Is ‘not Giving Azithromycin’ a Risk Factor for PICU Admission? - Arun Babu, Thirunavukkarasu; Narayanasamy, Dinesh Kumar (Journal of Nepal Health Research Council, 2021)
NA